Czech Broadside Ballads as Text, Art, Song in Popular Culture, c.1600-1900 - Fumerton, Patricia; Kosek, Pavel; Hanzelková, Marie (Amsterdam University Press, 2022)
This landmark collection makes a major contribution to the burgeoning field of broadside ballad study by investigating the hitherto unexplored treasure-trove of over 100,000 Central/Eastern European broadside ballads of the Czech Republic, from the 16th to the 19th century. Viewing Czech broadside ballads from an interdisciplinary perspective, we see them as unique and regional cultural phenomena: from their production and collecting processes to their musicology, linguistics, preservation, and more. At the same time, as contributors note, when viewed within a larger perspective-extending one's gaze to take in ballad production in bordering lands (such as Germany, Poland, and Slovakia) and as far Northwest as Britain to as far Southwest as Brazil-we discover an international phenomenon at work. Czech printed ballads, we see, participated in a thriving popular culture of broadside ballads that spoke through text, art, and song to varied interests of the masses, especially the poor, worldwide.